Pathological Findings of Highly Pathogenic Avian Influenza Virus A/Duck/Vietnam/12/2005 (H5N1) in Turkeys - Mehrabanpour, M.J.; Dadras, H.; Khodakaram-Tafti, A.; Rahimian, A.; Toffan, A. (International Journal of Poultry Science, 2007)
The aim of present study was to identify the clinical signs, gross and histopathological findings in turkeys experimentally infected with highly pathogenic avian influenza virus A/duck/Vietnam/12/2005 (H5N1). Specific pathogens free of white turkeys having 6 weeks old were inoculated with 0.1 mL of the virus with 105 EID50. Death was event at 3 DPI. Gross lesions observed after necropsy were splenomegaly, pulmonary edema, severe congestion in lungs, hyperemia in brain as well as cecal-tonsil and congestion in skeletal muscle. Histopathological finding were multi organ necrosis and/or inflammation. The most consistent and severely affected organs were spleen, lungs, brain, pancreas and cecal-tonsil. It would be worth to mention that the lungs and spleen were most affected organs, among the others grossly and histopathologically, However to our knowledge, this is the first description of histopathological finding of highly pathogenic avian influenza virus A/Duck/Vietnam/12/2005 (H5N1) in turkey.